A RESEARCH ON THE ASSOCIATION BETWEEN OBESITY AND NEW INFLAMMATION MARKERS IN ADULT FEMALES AND MALES - (:unkn) unknown (CARBONE EDITORE, 2019)
Objective: Obesity is a major healthcare problem in the world. Recently, it is shown that an association between obesity and inflammation. New inflammation markers have been started use in obesity. The aim of the present study was to detect the changes novel inflammation markers in our obesity patients. Method: Four hundred sixty-four patients (female = 363, male = 101) were used in study. Height was measured with barefoot on a flat surface. Whole body analysis was performed by bioempedence device (Tanita-BC418), and body weight, body mass index (BMI), fat percentage, fat mass(FM), fat-free mass(FFM) were detected. Blood parameters of the patients neutrophil, lymphocyte, platelet, monocyte, MPV data were obtained. NLR (neutrophil/lymphocyte ratio), LMR (lymphocyte/monocyte ratio), PLR (platelet/lymphocyte ratio), and SII(SII = platelet x neutrophil/lymphocyte) were calculated from these data. Statistical analysis of the data obtained through anthropometric measurements and blood parameters was conducted. Result: In female, it was detected that SII increases proportionally with body weight, BMI, fat percentage, fat mass, FFM, FMI(fat mass index), and NLR increases proportionally with fat percentage, fat mass; however, PLR ratio increases in proportion with fat percentage, fat mass, and FMI. In male, it was detected that SII increases with body weight, BMI, fat percentage, fat mass, FFM, FMI , and NLR increases with body weight, BMI, fat percentage , fat mass, FMI; however, LMR ratio increases with fat mass and FMI. Conclusion: In the present study we detected significant changes in inflammation markers in obesity, both female and male participants. We obtained significant outcomes on fat percentage, fat mass, fat-free mass, FMI and SII, NLR, LMR, and PLR levels individuallcy on both sexes. We believe that these parameters obtained from simple haemogram are found to be increased in relation to adipose tissue and may be important in progression and treatment of obesity.
Keywords: Obesity; fat mass; fat mass index; new inflammation biomarkers; MEAN PLATELET VOLUME; LYMPHOCYTE RATIO; PLATELET/LYMPHOCYTE RATIO; PREOPERATIVE LYMPHOCYTE; UNFAVORABLE PROGNOSIS; METABOLIC SYNDROME; DISEASE-ACTIVITY; MONOCYTE RATIO; ADIPOSE-TISSUE; NEUTROPHIL